Effect of innovative microwave assisted freezing (MAF) on the quality attributes of apples and potatoes - Jha, Piyush Kumar; Chevallier, Sylvie; Xanthakis, Epameinondas; Jury, Vanessa; LeBail, Alain (My University, 2020)
This study considered the effect of low energy microwave assisted freezing (MAF) on freezing time and quality attributes (microstructure, texture, drip loss and colour) of apple and potato. MAF of apples and potatoes was performed by applying constant microwave (MW) power (167 W/kg) and pulsed MW power (500 and 667 W/kg with 10 s pulse width and 20 s pulse interval resulting in an average power of 167 and 222 W/kg) during the freezing process. The temperature profile was monitored during the freezing process, and the microstructure was examined using X-ray micro-tomography and cryo-SEM. Other quality parameters such as texture, drip loss and colour were evaluated with thawed samples. It appeared that the freezing time was not affected by the MAF process. It is the first time that a MAF process is used for freezing plant-based products and showed that the application of microwaves during freezing process caused less freeze damage than the control condition.
Keywords: Apple; Drip loss; Freezing; Microstructure; Microwave; Potato; Quality; SEM